The law of kinship : anthropology, psychoanalysis, and the family in France - Robcis, Camille (Cornell University Press, 2013)
"Examines how French policy makers have called upon structuralist anthropology and psychoanalysis (specifically, the works of Claude Lévi-Strauss and Jacques Lacan) to reassert the centrality of sexual difference as the foundation for all social and psychic organization"--Author's Web site.